Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3174/ajnr.a2313
|View full text |Cite
|
Sign up to set email alerts
|

Subconjunctival Fat Prolapse and Dermolipoma of the Orbit: Differentiation on CT and MR Imaging

Abstract: BACKGROUND AND PURPOSE:Subconjunctival fat prolapse and dermolipoma of the orbit are unfamiliar to radiologists and yet should be differentiated because their treatments are different. The purpose of this study was to investigate the CT and MR imaging findings that distinguish these 2 conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 12 publications
(30 reference statements)
0
34
0
Order By: Relevance
“…2 In the largest series to date, Fry et al 1 describe 45 patients with dermolipomas, all of which were found to arise temporally. Mcnabb et al 2 and Kim et al 3 also found the dermolipoma to be in the temporal orbit in all patients studied in their series of 35 and 27 patients, respectively. Maeng et al 4 describe the only case we could find in the literature of a dermolipoma occurring medially and anterior to the palpebral conjunctiva that presented as a palpable right lower eyelid mass.…”
Section: Discussionmentioning
confidence: 84%
“…2 In the largest series to date, Fry et al 1 describe 45 patients with dermolipomas, all of which were found to arise temporally. Mcnabb et al 2 and Kim et al 3 also found the dermolipoma to be in the temporal orbit in all patients studied in their series of 35 and 27 patients, respectively. Maeng et al 4 describe the only case we could find in the literature of a dermolipoma occurring medially and anterior to the palpebral conjunctiva that presented as a palpable right lower eyelid mass.…”
Section: Discussionmentioning
confidence: 84%
“…1Y3 This weakening of the Tenon capsule allows the intraconal orbital fat to protrude anteriorly and can occur unilaterally or bilaterally. 5,6 Patients often present with cosmetic complaints and may also experience symptoms of dryness or discomfort. 2,4 If the lesion is large enough, it may cause formation of corneal dellen (distinct areas of corneal tissue thinning because of dehydration) secondary to exposure keratopathy.…”
mentioning
confidence: 99%
“…1 It typically manifests as a yellowcolored mass located superotemporal beneath the conjunctival tissue. 1,4,5 Subconjunctival HOF is assumed to occur because of a dehiscence of the Tenon capsule whether caused by age, injury, or surgery. 1Y3 This weakening of the Tenon capsule allows the intraconal orbital fat to protrude anteriorly and can occur unilaterally or bilaterally.…”
mentioning
confidence: 99%
See 2 more Smart Citations